Sains dalam Perspektif Barat dan Islam: Analisis Konseptual tentang Pengertian, Objek, Tujuan, dan Kegunaannya - Muhammad Andra Gracia Siregar; Salahuddin Harahap (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This article examines the concept of science from Western and Islamic perspectives, emphasizing the understanding, objects of study, goals, and uses of science in human life. This study is motivated by the differences in scientific paradigms between the modern Western tradition, which developed on the basis of rationality, empiricism, and the secularization of science, and the Islamic scientific tradition, which views science as an integral part of revelation, reason, and empirical reality. This research uses a qualitative method based on literature review with a descriptive-analytical and comparative approach to various classical and contemporary literary sources. The results of the study indicate that Western science tends to be anthropocentric, placing humans at the center of reality, and is oriented toward mastery of nature and the achievement of material progress. In contrast, science from an Islamic perspective is theocentric, placing God at the center of knowledge, and is directed toward achieving human well-being and a balance between this world and the afterlife. Despite these fundamental differences, both perspectives share similarities in the use of reason and empirical observation as primary instruments in the scientific process. This study is expected to provide a conceptual contribution to the development of the philosophy of science and efforts to integrate science in the contemporary era.